Login
Remember
Register
Home
All Activity
Q&A
Questions
Hot!
Unanswered
Tags
Categories
Users
Ask a Question
Ask a Question
Find x -1. (1) `-(1/7)^(-5) -: -(1/7)^(-7) = (-7)^x` (2) `(2/5)^(2x+6) xx (2/5)^3 =
0
votes
asked
Jan 18, 2022
in
8th-maths
by
Arun
(
1.7k
points)
Find x -1. (1) `-(1/7)^(-5) -: -(1/7)^(-7) = (-7)^x` (2) `(2/5)^(2x+6) xx (2/5)^3 = (2/5)^(x+2)`
marks3
chapter8
#sub
Please
log in
or
register
to answer this question.
0
Answers
Categories
All categories
Maths
(8.6k)
12th-maths
(0)
11th-maths
(0)
10th maths
(0)
9th-maths
(0)
8th-maths
(8.6k)
Science
(14)
Physics
(3.4k)
Related questions
Find x -1. (1) `-(1/7)^(-5) -: -(1/7)^(-7) = (-7)^x` (2) `(2/5)^(2x+6) xx (2/5)^3 =
Find x -1. (1) `-(1/7)^(-5) -: -(1/7)^(-7) = (-7)^x` (2) `(2/5)^(2x+6) xx (2/5)^3 =
Find x -1. (1) `-(1/7)^(-5) -: -(1/7)^(-7) = (-7)^x` (2) `(2/5)^(2x+6) xx (2/5)^3 =
Find x -1. (1) `-(1/7)^(-5) -: -(1/7)^(-7) = (-7)^x` (2) `(2/5)^(2x+6) xx (2/5)^3 =
Find x -1. (1) `-(1/7)^(-5) -: -(1/7)^(-7) = (-7)^x` (2) `(2/5)^(2x+6) xx (2/5)^3 =